Simulation model for pulse width modulation-voltage source inverter of three-phase induction motor - Salam Waley Shneen; Ahlam Luaibi Shuraiji (Institute of Advanced Engineering and Science, 2023)
Induction motor has been widely applied in many sectors, as it has the advantages of simplicity, toughness and can withstand hard environment conditions. The working of such motor in constant voltage/frequency (V/F) speed control method has been popular since the introduction of the power electronic devices, which consequently make the implementation of this method simpler and effectives. The V/F speed control is dominated choice for many applications, especially open loop control and also for closed loop control when the accuracy is not a crucial issue. This study deals with two cases of controlling open and close of the electronic switches. The first with equal intervals by placing regular pulses at the opening and closing periods, and the second using three-phase pulse width generator, through which the control of different periods is carried out according to the required control. Four models have been simulated in this study including, three-phase induction motor at constant torque (constant load) as well as at variable torque (variable load), modeling of PWM-VSI for three-phase induction motor at constant torque (constant load) as well as at variable torque (variable load). The results have shown that speed profile of the IM can be improved by controlling the invertor using PWM technique.